Ultilization of Shade as Microclimate Modification on Growth and Yield of Two Broccoli Varieties (Brassica oleracea var. italica) - Cahyarani, Putri Amanda; Herlina, Ninuk; Prasetianto, Mushoffan (Plantropica: Journal of Agricultural Science, 2024)
Broccoli (Brassica oleracea var. italica) is a plant with high economic value which is widely cultivated in Indonesia. Due to unfavorable environmental factors and improper cultivation methods, the supply of broccoli fluctuates, thus efforts must be made to boost production by altering the environment, adopting the use of paranets, and choosing the appropriate type. The study was carried out from February to April 2023 at an elevation of 460 meters above sea level in the Jatimulyo experimental field, Faculty of Agriculture, University of Brawijaya, Lowokwaru District, Malang City, East Java. Two treatments variety and shade were used in the study's nested design. Green magic and Lucky are among the primary plot variations, while no shade, 25% shade, 50% shade, and 75% shade are among the subplot variations related to shade.. The findings demonstrated that 25% shade was the ideal amount of cover to provide broccoli plants with the microenvironments they needed to growth and yield. Compared to the Lucky variety, which had a yield loss of 178.91 g.plant-1 (43.62%), the Green Magic variety was more suited to planting on medium plains, which Green magic loss of 22.26 g.plant-1 (6.99%).